Analysis of Effectiveness of Treatment of Meibomian Gland Dysfunction in Patients with Computer Vision Syndrome - Kavitha Chikkanayaknahalli Venugopal; Pavana Acharya; Shruthi Kavinamoole; Spoorti Mundinamani (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Aims: To evaluate association, stage and treatment efficacy of treating Meibomian Gland Dysfunction(MGD) in Computer Vision Syndrome(CVS) patients.  Setting: Department of ophthalmology, Hassan Institute of Medical Sciences, Hassan, Karnataka, India. Design: Prospective observational study. Materials and methods: Prospective study on 232 CVS patients were evaluated for MGD and randomly divided into groupA and B. GroupA were treated with tear supplements. GroupB were treated with azithromycin ointment and tear supplements. Efficacy was analysed at end of 3months. Statistical analysis: Data was analysed using descriptive statistics. Results: Among 232 CVS patients, MGD was found in 90(38.8%) patients . Among them, 38had stage1, 36had stage2 , 14had stage3 and 2patients had stage4 MGD. By the end of three months, in groupA, 34of 48 patients with stage1 and 2MGD were cured. In groupB, 36 of 42patients with all stages of MGD were cured. 100% of the CVS patients with stage1 , 66.7% of stage2 and 50% of the stage3 MGD improved completely with tear supplements alone whereas 25% of stage3MGD patients improved to stage1 and 25% of stage3 MGD did not improve at the end of three months. But, 100% of the CVS patients with stage1, 77.8% of stage2, 100% of stage3 improved completely and 1patient with stage4 MGD improved to stage1 by the end when treated with tear supplements and azithromycin ointment. Conclusion: 39% of CVS patients have MGD. So while treating CVS patient, its important to evaluate and treat MGD too. Tear supplements alone can be considered as a treatment option for CVS patients with stage1 and 2MGD whereas stage3 and 4MGD needs azithromycin ointment in addition to tear supplements for a good patient outcome.